A Blueprint for Creating Mentored, Collaborative Networks for Early-Career Physician-Scientists. Issue 1 (January 2021) - Mueller, Margaret G.; Andy, Uduak; Brennaman, Lisa; Dieter, Alexis A.; Kirby, Anna C.; Shepherd, Jonathan; Gregory, W. Thomas; Amundsen, Cindy L.
Abstract : Objectives: The objective is to improve the high-quality collaborative research of early-career investigators, the American Urogynecologic Society/Pelvic Floor Disorders Foundation funded and developed the Junior Faculty Research Network (JFRN). The purpose of this report is to describe the process of development of the network, discuss barriers, acknowledge accomplishments, and provide a framework for future collaborations. Methods: The development of the JFRN provided sponsorship and mentorship, supported collaboration, and created a network structure for early-career investigators. A request for applications was circulated, requiring a competitive submission process, and 6 physician-scientists were selected to participate in a multicenter trial whose initial focus was on the urinary microbiome and its interaction with sacral neuromodulation. Results: The JFRN infrastructure consisted of early-career investigators, senior advisors, and research support staff. Study development and roll-out progressed over monthly conference calls. Initial barriers included the development of institutional participation agreements, logistics of funding disbursement, and coordination of support staff. In addition to the inaugural research project, the network continued to collaborate, and the initial grant provided pilot data for a National Institutes of Health-funded project. Conclusions: The JFRN is a successful mentored collaborative of early-career investigators. The creation of this self-sustaining, independent research network may serve as a blueprint for other early-career physician-scientists to participate in productive multicenter research.